Disturbance or propagule pressure? Unravelling the drivers and mapping the intensity of invasion of free‐ranging dogs across the Atlantic forest hotspot. Issue 2 (11th December 2018) - Ribeiro, Fernando S.; Nichols, Elizabeth; Morato, Ronaldo G.; Metzger, Jean Paul; Pardini, Renata
Abstract: Aim: Identifying the drivers of biological invasions is crucial to predict the risk of invasion across broad spatial scales and to devise strategies to prevent invasion impacts. Here, we explore the relative importance and synergies between two key drivers—propagule pressure and landscape disturbance—in determining the invasion of native forest remnants by dogs, one of the most abundant, widely distributed, and harmful invasive species worldwide. Location: Brazilian Atlantic Forest. Methods: Combining a camera trap dataset (96 sites in forest remnants) and censuses of populations of dogs raised by humans across 12 landscapes (2, 830 ha each), we used N ‐mixture models that account for imperfect detection to confront alternative hypotheses of invasion drivers. We then used this empirical evidence to predict the intensity of dog invasion across the Atlantic Forest hotspot. Results: Propagule pressure (density of raised dogs, positive effect) and landscape disturbance (forest cover, negative effect) were equally important drivers of dog invasion, presenting additive rather than synergistic effects. Dogs invade forest remnants far from their homes, making the density of raised dogs the key component of propagule pressure (relative to dog spatial distribution). Forest cover was more important than either the length or density of forest edges, suggesting that both reduced area of forested barriers to long‐distance movements and increased proximity of forests to edges facilitate dog access to forests. Across the Atlantic Forest, the combination of high human population density and extensive deforestation makes dog invasion an additional and widespread threat. Main conclusion: Combined with available maps of priority areas for biodiversity conservation, our spatial prediction of dog invasion can help target areas for integrated management actions. These actions should go beyond measures to control dog populations and encompass the maintenance and restoration of native forests and strategic planning of afforestation through planted forests.